Local wisdom-based philosophy of science textbook - Mentari, Ana; Faisal, Emil El; Jaenuddin, Riswan; Alfiandra, Alfiandra; Camellia, Camellia; Sulkipani, Sulkipani; Rohman, Rohman (Jurnal Pendidikan PKN (Pancasila dan Kewarganegaraan), 2025)
This study aims to develop a textbook for the philosophy of science based on local wisdom. The research subjects were students of the Pancasila and Civics Education Study Program at Sriwijaya University who took the philosophy of science. The research method is R&D with steps; 1) preliminary study, 2) product development, and 3) product test. Through a preliminary study, the results of the needs analysis were obtained which stated that the philosophy of science textbooks used previously did not contain local wisdom, the number of books as learning resources was still minimal and students wanted unique learning resources, one of which contained the value of local wisdom. Thus, the research team must develop the textbook immediately. The textbook prototype was validated by material experts and linguists and then tested. The result of validation by linguists is 82.5% which means it is valid and the result of material validation by material experts is 84.4% which means it is valid. Tests on students, namely with one-to-one yielded 95% small group 91.2% and field evaluation 90%, and N-Gain 0.4 which means moderate. Thus, it means that textbooks are practical to use and have a potential impact to be used as a source of learning the value of local wisdom